The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/pcmr.12941
|View full text |Cite
|
Sign up to set email alerts
|

Support for increased cardiovascular risk in non‐segmental vitiligo among Egyptians: A hospital‐based, case–control study

Abstract: Background Data have been accumulating in the past few years that identify vitiligo as a disorder with systemic implications. Results and methods In this hospital‐based, cross‐sectional, case–control study, 50 patients with non‐segmental vitiligo and 50 age‐ and sex‐matched controls underwent analysis of serum lipid profile, oxidative stress biomarkers and carotid duplex. Hydrogen peroxide (H2O2) and malondialdehyde (MDA) were significantly higher in patients than controls (p‐value < .001, <.001, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“…OS is characterized by the excessive accumulation of oxidation products and inadequate antioxidants ( Chen et al, 2021 ). There is numerous evidence that patients with vitiligo have increased oxidation product like the lipid oxidation product malondialdehyde (MDA) and the oxidative DNA damage byproducts [8-hydroxy-2-deoxyguanosine (8-OHdG)] ( Wei et al, 2013 ; Vaseghi et al, 2017 ; Azzazi et al, 2021 ). In addition, patients with vitiligo have down-regulated enzymes, such as catalase (CAT) ( Agrawal et al, 2014 ) and dysregulated superoxide dismutase (SOD) ( Koca et al, 2004 ; Khan et al, 2009 ; Ozel Turkcu et al, 2014 ), and abnormal non-enzyme defense to oxidants like the total antioxidant capacity (TAC) ( Hayran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…OS is characterized by the excessive accumulation of oxidation products and inadequate antioxidants ( Chen et al, 2021 ). There is numerous evidence that patients with vitiligo have increased oxidation product like the lipid oxidation product malondialdehyde (MDA) and the oxidative DNA damage byproducts [8-hydroxy-2-deoxyguanosine (8-OHdG)] ( Wei et al, 2013 ; Vaseghi et al, 2017 ; Azzazi et al, 2021 ). In addition, patients with vitiligo have down-regulated enzymes, such as catalase (CAT) ( Agrawal et al, 2014 ) and dysregulated superoxide dismutase (SOD) ( Koca et al, 2004 ; Khan et al, 2009 ; Ozel Turkcu et al, 2014 ), and abnormal non-enzyme defense to oxidants like the total antioxidant capacity (TAC) ( Hayran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been a notorious factor involved in the development of various diseases, including vitiligo and metabolic syndrome, through the generation of reactive oxygen species (ROS). ROS plays a vital role in cellular events such as inflammatory response, cell growth alteration, and apoptosis [ 12 ]. Enzymatic and non-enzymatic antioxidants such as superoxide dismutase, glutathione peroxidase, and catalase are present in melanocytes whose primary function is to prevent oxidative damage.…”
Section: Reviewmentioning
confidence: 99%
“…Koca et al, in their study, showed excess free radical generation leading to peroxidative damage mediated by increased oxidative destruction of polyunsaturated fatty acid of phospholipids [ 14 ]. This oxidative destruction was supported by increased levels of malondialdehyde (MDA) and H 2 O 2 [ 12 , 14 , 15 ]. Azzazi et al and Khan et al also found decreased total antioxidant capacity in patients compared to controls.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Karadag et al are concordant with the abovecited papers, showing lower HDL concentration, increased LDL/HDL ratio, and higher insulin resistance as measured with homeostatic model assessment-IR (HOMA-IR) [62]. A recent study by Azzazi et al has shown that a subset of patients with vitiligo is at a higher risk of developing dyslipidemia and atherosclerosis, which might increase their future risk for the development of cardiovascular disease, by means of analysis of the serum lipid profile, oxidative stress biomarkers, and carotid duplex [63]. The possible alterations of the lipid profile seem not to be limited to adults as Pietrzak et al have shown increased LDL, decreased HDL, and increased LDL/HDL ratio and triglycerides in vitiligo-affected children [64].…”
Section: Metabolic Comorbidities In Vitiligomentioning
confidence: 99%